Changing influenza activity in the Southern hemisphere countries during the COVID-19 pandemic - Jeehyun Kim; Raquel Elizabeth Gómez Gómez; Kwan Hong; Sujin Yum; Jieun Jang; Byung Chul Chun (International Journal of Infectious Diseases, 2021)
Introduction: While the reduction in influenza cases in the Northern hemisphere in 2020 has been widely reported, the influenza transmission dynamics in the Southern hemisphere remain uncharacterized. Methods: This study analysed the change in influenza-positive proportion (IPP) between 2010–2019 and 2020 in countries in the Southern hemisphere with ≤40% missing IPP data in FluNet to assess how coronavirus disease 2019 (COVID-19) relates to influenza activity. The analysis considered the incidence of COVID-19 reported by the World Health Organization and the implementation date of non-pharmaceutical interventions (NPIs) reported by the Oxford COVID-19 Government Response Tracker. Results: In each of the seven included countries, the average IPP was lower in 2020 than in 2010–2019 (P < 0.01), with the largest difference being 31.1% (95% confidence interval 28.4–33.7%). In Argentina, Bolivia, Chile and South Africa, higher IPPs were observed during epidemiological weeks 4–16 in 2020 compared with the same weeks in 2010–2019. The IPP increased after NPIs were implemented in Argentina and South Africa, but started to decline in Bolivia, Chile, Madagascar and Paraguay before NPI implementation. Conclusions: Influenza burden and activity decreased in 2020 in the Southern hemisphere. The temporal decline in influenza activity varied between countries.